The Biopsychosocial Spectrum of Osteoarthritis Management in Primary Care : A Case Report - Kuntadi, Muhammad; Andarini, Sri; Wuri, Kinanthi (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2025)
Osteoarthritis (OA), a prevalent degenerative joint disease, poses significant challenges in primary care due to its chronic nature and multifaceted impact on patients' lives. This case report highlights the importance of a comprehensive, patient-centered approach to managing OA, integrating biomedical, psychological, and social considerations within the family medicine framework. A 60-year-old male, a civil servant and single parent, presented with chronic, worsening left knee pain and concurrent left shoulder pain of three months' duration, alongside a history of controlled hypertension. Initial self-management with topical analgesics and knee support provided minimal relief. Clinical assessment, based on ACR and ICPC criteria, led to a diagnosis of left genu osteoarthritis and left shoulder osteoarthritis. The management strategy adopted a holistic perspective, acknowledging the patient's physical symptoms, his concerns as a single parent, and the psychological burden of his condition. Non-pharmacological interventions, including lifestyle modifications, ergonomic advice, and regular light exercise, were emphasized. Pharmacological treatment involved analgesics, while a referral to an orthopedic specialist was initiated due to persistent symptoms. The Family APGAR score indicated good family function, crucial for supporting comprehensive interventions. This case underscores how family dynamics and psychosocial stressors influence chronic disease presentation and management in primary care. This case illustrates that effective OA management extends beyond pharmacological interventions to encompass a thorough understanding of the patient's biopsychosocial context. A robust family medicine approach, integrating patient education, lifestyle modification, and psychosocial support, is crucial for improving outcomes and enhancing the quality of life for individuals with chronic conditions, such as osteoarthritis.